2011
DOI: 10.1001/jama.2011.124
|View full text |Cite
|
Sign up to set email alerts
|

Serum Bilirubin and Risk of Respiratory Disease and Death

Abstract: Among patients with normal-range bilirubin levels in primary care practices, relatively higher levels of bilirubin were associated with a lower risk of respiratory disease and all-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
183
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(202 citation statements)
references
References 31 publications
15
183
4
Order By: Relevance
“…These associations are also reported in individuals with Gilbert syndrome (9,10). Several findings suggest preventive effects of unconjugated bilirubin (UCB) on cancer development, showing that the prevalence and incidence of lung and colon cancer is reduced with increasing circulating UCB concentrations (7,11). Recently, a possible protective role of the UGT1A1 Ã 28 allele on colorectal cancer (CRC) was detected and patients with CRCs had lower serum bilirubin levels than controls (10).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…These associations are also reported in individuals with Gilbert syndrome (9,10). Several findings suggest preventive effects of unconjugated bilirubin (UCB) on cancer development, showing that the prevalence and incidence of lung and colon cancer is reduced with increasing circulating UCB concentrations (7,11). Recently, a possible protective role of the UGT1A1 Ã 28 allele on colorectal cancer (CRC) was detected and patients with CRCs had lower serum bilirubin levels than controls (10).…”
Section: Introductionmentioning
confidence: 90%
“…Importantly, epidemiologic evidence suggests a preventive role for bilirubin in disease development, specifically in regard to cardiovascular disease and cancer (7,8). These associations are also reported in individuals with Gilbert syndrome (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…• Relatively higher levels of bilirubin were associated with a lower risk of pulmonary disease and all-cause mortality (23). Bilirubin possesses anti-oxidant, anti-inflammatory, and anti-proliferative effects (24).…”
Section: Other Candidate Biomarkers In Copdmentioning
confidence: 99%
“…The antioxidant properties of this enzyme are mediated largely via intracellular generation of free bilirubin, which functions physiologically to inhibit certain NADPH oxidase complexes [43][44][45][46]. Intriguingly, in a massive prospective study in the UK, serum levels of bilirubin at baseline were found to correlate inversely with risk for both COPD and lung cancer, after controlling for smoking habit [47]. Likewise, in a case -control study, serum free bilirubin was lower in patients with COPD than without [48].…”
Section: Complementary Protection From Spirulina?mentioning
confidence: 99%